Molecular Genetics in Neuroblastoma Prognosis - Margherita Lerone; Marzia Ognibene; Annalisa Pezzolo; Giuseppe Martucciello; Federico Zara; Martina Morini; Katia Mazzocco (MDPI AG, 2021)
In recent years, much research has been carried out to identify the biological and genetic characteristics of the neuroblastoma (NB) tumor in order to precisely define the prognostic subgroups for improving treatment stratification. This review will describe the major genetic features and the recent scientific advances, focusing on their impact on diagnosis, prognosis, and therapeutic solutions in NB clinical management.